PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. AN-NUR KANGGRAKSAN CIREBON - Wiwit Kartikasari; Diana Dewi (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2017)
Problems in this research is the workload given by PT. An-Nur Kanggraksan Cirebon to many employees that burdensome employees so that the work is completed with extra time (overtime), while the workplace environment is felt by employees is still less comfortable resulting in decreased even though not significantly reduced employee performance. This study aims: 1) To describe data about the effect of workload on employee performance PT. An-Nur Kanggraksan Cirebon. 2) To describe data about the influence of work environment on employee performance PT. An-Nur Kanggraksan Cirebon. 3) To describe data about the influence of workload and work environment simultaneously on the performance of employees of PT. An-Nur Kanggraksan Cirebon. The data collecting of this research is done through questionnaire to 50 employees as the research sample. While the data processing using statistical data analysis using multiple linier regression analysis method. The conclusions of this study are: 1) Work load affect the performance of employees at PT. An-Nur Kanggraksan Cirebon based on the results of data analysis is known to prove at the level of significance of ? = 0.05 (5%) ie with a tcount of 2.239> ttable of 1.998 meaning significant. Thus if the workload is increasing then the performance of employees participate in the increase. 2) Work environment affect on employee performance at PT. An-Nur Kanggraksan Cirebon based on the results of data analysis is known to prove at the level of significance of ? = 0.05 (5%) ie with a t count of 2.184> ttable of 1.998 meaning significant. Thus the improved and conducive work environment hence increasing the performance of employees. 3) Meanwhile, workload and work environment are proven jointly affect the performance of employees at PT. An-Nur Kanggraksan Cirebon based on the results of data analysis known this result proved to be believed at the level of significance of ? = 0.05 (5%) with the value of Fhitung 6.187> Ftable of 3.14 means significant. If the workload and work environment are synergized in improving employee performance then the result obtained is the influence of workload and work environment on employee performance is quite meaningful. Key words : workload, work environment and employee performance.